Information systems impact measurement model in MYPES in Peru - Bernal Guio, Adolfo (2018)
Companies make investments in Information Systems for specific purposes in the market, this is how this measurement has become a cause of misunderstanding when the company needs measuring the results of the use of information systems within the organization.This objective of this research is to propose a model to measure the impact of the information systems for MyPES on Peru, based on initial model proposed by Gable and modified by Alshardan, including new items to consider in measurement impact for the current environment for MyPES.The proposed model is validated through surveys, which evaluate each dimension of the selected model. 12 MyPES of Metropolitan Lima were considered as a representative sample for the case of the study obtaining in them the favorable results.